The machinery of #techno-colonialism crafting "democracy." A glimpse into digital sub-netizenship in Mexico. Issue 8 (17th November 2021) - Durán Matute, Inés; Camarena González, Rodrigo
ABSTRACT: This article elaborates the concepts of techno-colonialism and sub-netizenship to explore the renewal of colonial processes through the digitalization of "democracy." Techno-colonialism is conceived as a frame – adopted consciously and unconsciously – that shapes capitalist social relations and people's political participation. Today, this frame appeals to the idealized netizen, a global, free, equal and networked subject that gains full membership to a political community. Meanwhile, sub-netizenship is the novel political subordination because of race, ethnicity, class, gender, language, temporality, and geography within a global matrix that crosses the analogue-digital dimensions of life. This techno-colonialism/sub-netizenship dynamic manifested in the experience of Marichuy as an indigenous independent precandidate for the Mexican presidential elections of 2018. In a highly unequal and diverse country, aspirants required a tablet or smartphone to collect citizen support via a monolinguistic app only accessible to Google or Facebook users. Our analysis reveals how some individuals are excluded and disenfranchised by digital innovation but still resist a legal system that seeks to homogenize them and render them into legible and marketable data.